Unexplained hemolytic anemia of pregnancy: Case report with review of related literature - Sharma, Paban; Sthapit, Rekha (Nepal Journal of Obstetrics and Gynaecology, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> We present a case of a multipara lady who developed hemolytic anemia during pregnancy with spontaneous remission after delivery. She was managed with low dose steroid for hemolysis during pregnancy with good feto-maternal outcome. Despite extensive investigations carried out to determine the cause, they remained in vain. Very few of such cases have been described in the literature, which merits its presentation. Key words: Hemolytic anemia, pregnancy doi:10.3126/njog.v3i1.1441 NJOG 2008 May-June; 3(1): 49 - 50